Navigating psychological membership in sport organizations: Exploring sport employees' identities. Issue 2 (3rd April 2023) - Oja, Brent D.; Gordon, Brian S.; Hazzaa, Rammi N.
Abstract: This study was created to examine sport employees' social identities. While a clearer understanding of sport fans' social identities exists, there is a gap in the literature pertaining to the identification processes of sport employees–including the influence of fandom. As such, this study is positioned to examine how and why sport employees identify with their sport organizations. The study was grounded in a hermeneutic phenomenology approach to gather deep and rich data concerning sport employees' lived experiences of working in the sport industry. Specifically, semi-structured interviews were conducted with 18 full-time sport employees from a variety of American sport sectors. A thematic analysis of the transcribed interviews was used to develop a total of four themes that explored the meanings of the self-concepts of participants, the symmetry between their self-views and sport organizations, the experience of a sense of belonging with a sport organization, and the interplay between sport employees and fans. The results of the study support previous work suggesting that sport employees have a distinct social identification process with their sport organizations. In terms of potential outcomes, the application of social identification in the sport workplace could lead to enhanced employee and organizational performance, as participants were willing to engage in labor, primarily in the form of organizational citizenship behaviors, that supported the functionality their sport organizations. Lay summary: This study explored sport employees' sense of fandom and membership with sport organizations. During interviews, participants viewed sport and competition as important aspects of themselves and working in sport organizations reinforced such ideals. Further, there is potential for improved employee and organizational performance when sport employees identify with their organization. Implications for practice: Employees' social identities can be supported by emphasizing competition Identified sport employees value their contributions and will increase work efforts Sport organizations can leverage identified employees to enhance performance by promoting an atmosphere of helping behaviors and valuing organizational outcomes